Close packing UHPGC mix proportion design method considering reaction

By considering the close packing method of reactions, the problems of long design cycle of UHPGC mix ratio, lack of theoretical guidance, insufficient real state reflection, and poor performance compliance are solved, and more scientific and accurate mix ratio design is achieved, improving the performance compliance effect.

CN119905183APending Publication Date: 2025-04-29HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510066832.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing ultra-high performance geopolymer concrete (UHPGC) mix ratio design methods have problems such as long mix ratio formation cycle, lack of scientific theoretical guidance, inability to reflect the real state of concrete, and poor performance and performance.

Method used

A close-packaged UHPGC mix ratio design method considering the reaction is adopted. By determining the target compressive strength and fluidity, defining the precursor powder and alkali exciter, determining the reaction time and reaction degree of alkali excitation, selective dissolution method and XRD refining quantitative analysis are used to determine the reaction product density, calculate the particle size correction coefficient, and then determining the mix ratio of UHPGC.

Benefits of technology

This method can more accurately reflect the actual stacking state of concrete, improve the scientificity and accuracy of mix ratio design, shorten the design cycle, and improve the effect of performance compliance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905183A_ABST
    Figure CN119905183A_ABST
Patent Text Reader

Abstract

The invention relates to a close packing UHPGC mix proportion design method considering reaction, which comprises the following steps: firstly, respectively reacting precursor powder with an alkali activator, and testing the reaction time, reaction degree and reaction product density of the precursor powder by reaction heat test, selective dissolution and XRD quantitative analysis so as to determine the particle size of the reacted precursor powder; the particle size of the reacted particles and the particle size of the aggregate are used for close packing to calculate the mix proportion of the UHPGC, the mix proportion of the UHPGC is calculated based on the particle size of the reacted particles, the influence of water and the alkali activator on the precursor powder is considered, the actual packing state of the UHPGC can be better reflected and is closer to the real packing state, and the accuracy of the UHPGC is improved. And the accuracy and scientificity of UHPGC mix proportion design by using a close packing method are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete mix design, and in particular to a reaction-considered densely packed ultra-high performance geopolymer concrete (UHPGC) mix design method. Background Art

[0002] Ultra-high performance concrete (UHPC) has represented a significant advancement in modern building materials since the 20th century, characterized by superior compressive strength (>120MPa), flexural strength (>20MPa) and excellent durability. However, the production of UHPC usually requires the use of 800-1100kg / m 3 of ordinary Portland cement, which is 2 to 3 times the amount required for ordinary concrete, exacerbating the greenhouse effect and causing significant environmental problems. Therefore, more and more researchers have begun to explore low-carbon alternative materials to reduce the environmental burden of UHPC. Geopolymer, as a cementitious material without clinker, has become a potential substitute for ordinary Portland cement due to its mechanical properties equivalent to or better than ordinary Portland cement. Geopolymer is synthesized by alkali activation of powder materials rich in SiO2, Al2O3 and CaO at room temperature to 90°C. The most commonly used precursors include kaolin, fly ash, blast furnace slag, rice husk ash, etc., most of which are by-products of heavy industry. Due to the non-calcination process of geopolymer, its carbon dioxide emissions are about 60% lower than that of ordinary Portland cement, so it has significant environmental protection benefits.

[0003] The widespread application of ultra-high performance geopolymer concrete (UHPGC) faces several key challenges. On the one hand, due to its extremely low water-binder ratio, it has problems with poor fluidity and fast setting speed. On the other hand, adjusting the raw material composition to optimize working performance will affect strength; at the same time, factors such as the diversity of alkali activators, the high complexity of geopolymer reaction mechanisms and reaction products further increase the difficulty of UHPGC mix design, and it is even more difficult to achieve performance requirements. Therefore, UHPGC lacks an accurate and efficient design method. In order to promote the application of UHPGC, it is necessary to establish a scientific mix design method.

[0004] At present, there are three main methods for the mix design of UHPGC: empirical method, target strength method and mathematical model method. The empirical method relies on experience and adjusts the mix ratio of concrete through multiple trial mixes in the laboratory to achieve the target performance. This method has no theoretical support, a long trial mix cycle, consumes a lot of manpower and material resources, and the mix ratio is not universal, so it cannot be promoted and applied. The target strength method is a method that uses the target strength as the design indicator and the Ca / (Si+Al) ratio and Si / Al ratio in alkali-activated concrete as the link for mix design. The determination of the amount of precursor powder in this method is only applicable to the case where Si / Al=2.4 and 3.8 and Ca / (Si+Al)=0.46, and the scope of application is relatively narrow. The mathematical model method is based on the theory of the most densely packed particles. This method only adjusts the ratio of each powder component to achieve the dense packing of each material component, thereby obtaining concrete with ultra-high performance. Among the mathematical model methods, the method based on the Anderson & Andreason (MAA) model is widely used due to its simplicity and accuracy, as shown in formulas (1) and (2):

[0005]

[0006] Where P(D) is the volume fraction of particles with a diameter smaller than D;

[0007] D is the particle size after the reaction; D min is the diameter of the smallest particle in the system;

[0008] D max is the diameter of the largest particle in the system

[0009] q is the distribution modulus (0.2-0.5);

[0010] In order to maximize the packing density of the system, it is necessary to minimize the error between the target value and the fitted value, that is, to satisfy formula (1):

[0011]

[0012] in and They represent the percentage of particles between the i-th particle size and the i+1-th particle size in the actual stacking curve and the ideal stacking curve, respectively. RSS is the residual sum of squares, and TSS is the total sum of squares.

[0013] However, the particle accumulation of concrete is completed in a wet state, accompanied by hydration reaction or alkali-induced reaction, particle agglomeration, water film wrapping, etc. Therefore, the dense packing mix design theory based on the MAA model lacks consideration of several important factors, such as the reaction degree of the precursor powder alkali-induced reaction, the reaction products and the influence of the presence of liquid in the system on the particle accumulation, and cannot accurately reflect the actual packing state.

[0014] In summary, the existing UHPGC mix design methods have the problems of long mix formation cycle, lack of scientific theoretical guidance, inability to reflect the true state of concrete, and poor performance compliance. Summary of the invention

[0015] The purpose of the present invention is to solve the problems of the existing ultra-high performance geopolymer concrete mix design method, such as long mix ratio formation cycle, lack of scientific theoretical guidance, inability to reflect the real state of concrete, and poor performance compliance, and to provide a tightly packed UHPGC (ultra-high performance geopolymer concrete) mix design method taking reaction into consideration.

[0016] To achieve the above object, the technical solution of the present invention is:

[0017] A method for designing a close-packed UHPGC mix ratio considering reactions, the steps of the design method are:

[0018] Step 1: Determine the target compressive strength and target fluidity of the UHPGC to be prepared, as well as the maintenance system;

[0019] Step 2: Define the powder that can react with the alkaline activator as the precursor powder, and determine the type of UHPGC precursor powder;

[0020] Step 3: Determine the type of alkali activator and the molar number of Na2O in different types of alkali activators, and simultaneously determine the alkali-binder ratio (N / B) and the water-binder ratio (W / B); wherein the alkali-binder ratio is the ratio of the mass of Na2O contained in the alkali activator used in the UHPGC mix ratio to the total mass of the precursor powder, and the water-binder ratio is the ratio of water to the total mass of the precursor powder;

[0021] Step 4: Determine the alkali excitation reaction time of each precursor powder:

[0022] The reaction heat test method is used to determine the reaction time when each precursor powder reacts with each alkaline activator to reach the exothermic steady state;

[0023] The precursor powders of different types are set to have the same mass, denoted as A0, and the mass of sodium oxide in each alkaline activator is set to 4% A0;

[0024] Step 5: Determine the degree of alkali excitation reaction of the precursor powder:

[0025] Determine the alkali excitation reaction time of each precursor powder and each alkali exciter in step 4, and use it as the termination point of the reaction equilibrium to perform the alkali excitation reaction. After the reaction equilibrium is reached, filter, dry, and grind, and then perform a two-step selective dissolution method to determine the alkali excitation reaction degree of each precursor powder. Different solvents can be selected for each precursor powder.

[0026] The process of the two-step selective dissolution method is:

[0027] The first step is to select a first selective solvent that cannot dissolve the precursor powder and the alkali-activated product CASH gel, but can dissolve the alkali-activated product NASH gel, and dissolve the sample that has reached the reaction equilibrium termination point in the first selective solvent for 1 hour; after the dissolution is completed, filter and dry, and record the mass as M1;

[0028] Step 2: Select a second selective solvent that cannot dissolve the precursor powder but can dissolve the alkali-activated product CASH gel, and dissolve the material filtered and dried in the first step in the second selective solvent for 1 hour. After dissolution, filter and dry to constant weight, and record the mass as M3;

[0029] Then, according to formulas (3)-(5), the mass fraction C of NASH gel generated at reaction equilibrium is obtained: nash and CASH gel mass fraction C cash and the degree of reaction γ;

[0030] C nash =(M0-M1) / M0×100% (3)

[0031] C cash =(100%-C nash )×(M2-M3) / M2 (4)

[0032] γ=C nash +C cash (5)

[0033] Wherein, M2 is the mass of material used in the second step of selective dissolution; M0 is the mass of sample used in the first step of selective dissolution;

[0034] Step 6: Determine the weighted average density of the precursor powder alkali excitation reaction product:

[0035] XRD refinement and quantitative analysis were performed on the powder sample after the reaction in step 5 reached the termination point to determine the mass fraction W of the amorphous phase after the precursor alkali excitation reaction. a And the mass fraction of the main crystalline phase material W i According to formula (9), the weighted average density ρ of the base-excited reaction product is determined product ;

[0036] ρ product =W a ·ρ a +W i ·ρ i (9)

[0037] Among them, ρ a+ is the density of amorphous phase, ρ i is the density of the main crystalline phase material;

[0038] Step 7: Use a laser particle size analyzer to determine the particle size distribution D of the precursor powder and aggregate;

[0039] Step 8: Calculate the original density ρ of each precursor powder origin The reaction coefficient is obtained by subtracting the corresponding ratio from 1 to the weighted average density of the reaction products of the precursor powder and different types of alkali activators determined in step 6 and then multiplying the reaction degree of the corresponding alkali activator precursor powder by the molar composition coefficient of the corresponding type of alkali activator in the UHPGC formula;

[0040] Subtract the reaction coefficients corresponding to all types of alkaline activators from 1 to obtain the particle size correction coefficient of the precursor powder;

[0041] The product of the correction coefficient and D is taken as the particle size D' of the precursor powder after the reaction;

[0042] Step 9: According to the particle size D' of the precursor powder after reaction determined in step 8 and the original particle size of the aggregate, the diameter of the largest particle and the diameter of the smallest particle in the system are determined, and substituted into the MAA model to obtain the volume fraction P(D') of particles smaller than D', and then obtain the mix ratio of UHPGC;

[0043] Step 10: Based on step 9, select the steel fiber volume fraction with the best compressive strength and fluidity as the final steel fiber dosage, and calculate the steel fiber mass M 钢纤维 ;

[0044] Step 11: Carry out trial mix according to the final formula determined in step 10 and evaluate whether the compressive strength of the concrete is not less than the target compressive strength. If it is not less than, end the mix design; if it is less than, return to step 3 to adjust the mix parameters and the amount of each component.

[0045] Furthermore, the number of types of the base activators is not less than 1.

[0046] Furthermore, the alkaline activator is sodium silicate and sodium hydroxide, and the particle size D' of each precursor powder after the reaction is expressed by formula (10):

[0047]

[0048] in, α1 and α2 are the molar composition coefficients of sodium oxide in sodium hydroxide and sodium silicate, respectively; n1(Na2O) and n2(Na2O) are the amounts of Na2O contained in sodium hydroxide and sodium silicate in the actual mix ratio; γ1 and γ2 represent the degree of reaction of the precursor powder when sodium hydroxide and sodium silicate are used as alkaline activators, respectively; ρ origin is the original density of the precursor powder, ρ product1 , ρ product2 are the weighted average densities of the precursor powder reaction products when sodium hydroxide and sodium silicate are used as alkaline activators, respectively.

[0049] Furthermore, the XRD refinement quantitative analysis uses α-Al2O3 as an internal standard. After the precursor powder and the alkaline activator react to the termination point, they are filtered, dried to constant weight and ground. The ground powder is weighed and 10% of the powder mass of α-Al2O3 is added and continued to grind so that the internal standard and the powder are fully mixed, and then XRD refinement analysis is performed; the main crystalline phase refers to the crystalline phase whose mass accounts for not less than 5% in the XRD refinement analysis sample.

[0050] Furthermore, in the two-step selective dissolution method, each precursor powder can select a different solvent, and the order of the first and second steps of selective dissolution can be swapped. The first selective dissolution agent after the swap is a solvent that cannot dissolve the precursor powder and NASH gel, but can dissolve the alkali-excited product CASH gel. The sample that reaches the reaction equilibrium termination point is dissolved in the first selective dissolution agent for 1 hour; after the dissolution is completed, the mass is recorded as M1 after filtration and drying, which is used to calculate the mass fraction C of CASH gel. cash ;

[0051] At this time, the second selective dissolving agent cannot dissolve the precursor powder, but can dissolve the alkali-activated product NASH gel. The material filtered and dried in the first step is dissolved in the second selective dissolving agent for 1 hour. After the dissolution is completed, it is filtered and dried to a constant weight. The mass is recorded as M3, which is used to calculate the mass fraction C of NASH gel. nash .

[0052] Furthermore, the first selective dissolving agent is at least one of salicylic acid-methanol solution and picric acid-methanol-water solution; the second selective dissolving agent is at least one of dilute hydrochloric acid, EDTA solution and EDTA / DEA solution.

[0053] Furthermore, in the step nine, when determining the mix ratio of UHPGC, the mass percentage range of silica fume is set, and the mix ratio of UHPGC is determined under this premise.

[0054] Furthermore, the curing system is high temperature curing or steam curing, and the curing temperature is any temperature between 50°C and 90°C; preferably, the curing system also includes a stirring system;

[0055] The pore size of the filter assembly used in the filtration is not less than 0.45 μm;

[0056] The target compressive strength is 100MPa-150MPa.

[0057] The curing system in the present invention is high temperature curing or steam curing. The curing temperature can be determined according to the mechanical property requirements of the UHPGC. Generally, any temperature between 50°C and 90°C is selected. The preferred curing system is 80°C oven curing for 48 hours.

[0058] Furthermore, step one also includes a stirring system, including the following steps:

[0059] Step 1: Mix the precursor powder and aggregate and stir for 2 minutes;

[0060] Step 2: Add the alkaline activator determined in step 3 and stir at low speed (140r / min) for 2 minutes;

[0061] Step 3: Add the steel fiber determined in step 10 and stir at high speed (280r / min) for 1 minute. The test method is: the compressive strength test is carried out using a 50×50×50mm 3 Cube test block, the test block loading system is 0.6MPa / s.

[0062] Preferably, the short straight steel fiber has a diameter of 0.2 mm and a length of 13 mm.

[0063] Furthermore, the total amount of precursor powder in step 2 is M 前总 =800-1100kg / m 3 .

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] The outstanding essential features of the present invention are:

[0066] The mix design method of the present invention firstly reacts precursor powders with alkali activators respectively, and tests the reaction time, reaction degree and reaction product density of the precursor powders by reaction heat test, selective dissolution and XRD quantitative analysis, so as to determine the particle size of the precursor powders after the reaction, and then uses the particle size of the particles after the reaction and the particle size of the aggregate to perform close stacking to calculate the mix ratio of UHPGC. The UHPGC mix ratio calculated based on the particle size after the reaction takes into account the influence of water and alkali activators on the precursor powders, can better reflect the actual stacking state of UHPGC, is closer to the real stacking state, and improves the accuracy and scientificity of UHPGC mix design using the close stacking method.

[0067] The significant improvements of the present invention are:

[0068] (1) The present invention is applicable to the mix design of UHPGC with a compressive strength between 100MPa and 150MPa. The method overcomes the problems of the UHPGC mix design method, such as the long formation cycle of the test and trial method, the large amount of manpower and material resources consumed, the lack of scientific theoretical guidance, and the inability of the close stacking method to reflect the real state of concrete. The method has a good performance improvement effect and lays a foundation for the promotion and application of UHPGC.

[0069] (2) The process of mix design of the present invention is applicable to the mix design of UHPGC using various precursor powders, and is also applicable to concrete of other cementitious systems. In addition, the process of the method is not only applicable to UHPGC, but also to other types of fiber-reinforced geopolymer concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 It is a schematic flow chart of the ratio design method of the present invention;

[0071] Figure 2 is the particle size distribution diagram of the raw material;

[0072] Figure 3 It is the fitting result of the raw material component ratio in the comparative example and each example determined based on the particle close packing theory. DETAILED DESCRIPTION

[0073] The technical solution of the present invention is not limited to the following embodiments, but also includes any reasonable combination of the specific embodiments. The following embodiments are only used to further explain the present invention, but are not used as a limitation on the protection scope of this application.

[0074] The present invention provides a method for designing a mix ratio of a densely packed ultra-high performance geopolymer concrete (UHPGC) considering a reaction, comprising the following steps:

[0075] Step 1: Determine the target compressive strength and target fluidity of the UHPGC to be prepared, as well as the maintenance system;

[0076] Step 2: Define the powder that can react with the alkaline activator as the precursor powder, and determine the type of UHPGC precursor powder;

[0077] Step 3: Determine the type of alkali activator and the molar number of Na2O in different types of alkali activators, and simultaneously determine the alkali-binder ratio (N / B) and the water-binder ratio (W / B); wherein the alkali-binder ratio is the ratio of the mass of Na2O contained in the alkali activator used in the UHPGC mix ratio to the total mass of the precursor powder, and the water-binder ratio is the ratio of water to the total mass of the precursor powder;

[0078] Step 4: Determine the alkali excitation reaction time of each precursor powder:

[0079] The reaction heat test method is used to determine the reaction time when each precursor powder reacts with each alkaline activator to reach the exothermic steady state;

[0080] The precursor powders of different types are set to have the same mass, denoted as A0, and the mass of sodium oxide in each alkaline activator is set to 4% A0;

[0081] Step 5: Determine the degree of alkali excitation reaction of the precursor powder:

[0082] Determine the alkali excitation reaction time of each precursor powder and each alkali exciter in step 4, and use it as the termination point of the reaction equilibrium to perform the alkali excitation reaction. After the reaction equilibrium is reached, filter, dry, and grind, and then perform a two-step selective dissolution method to determine the alkali excitation reaction degree of each precursor powder. Different solvents can be selected for each precursor powder.

[0083] The process of the two-step selective dissolution method is:

[0084] The first step is to select a first selective solvent that cannot dissolve the precursor powder and the alkali-activated product CASH gel, but can dissolve the alkali-activated product NASH gel, and dissolve the sample that has reached the reaction equilibrium termination point in the first selective solvent for 1 hour; after the dissolution is completed, filter and dry, and record the mass as M1;

[0085] Step 2: Select a second selective solvent that cannot dissolve the precursor powder but can dissolve the alkali-activated product CASH gel, and dissolve the material filtered and dried in the first step in the second selective solvent for 1 hour. After dissolution, filter and dry to constant weight, and record the mass as M3;

[0086] Then, according to formulas (3)-(5), the mass fraction C of NASH gel generated at reaction equilibrium is obtained: nash and CASH gel mass fraction C cash and the degree of reaction γ;

[0087] C nash =(M0-M1) / M0×100% (3)

[0088] C cash =(100%-C nash )×(M2-M3) / M2 (4)

[0089] γ=C nash +C cash (5)

[0090] Wherein, M2 is the mass of material used in the second step of selective dissolution; M0 is the mass of sample used in the first step of selective dissolution;

[0091] Step 6: Determine the density of the precursor powder alkali excitation reaction product:

[0092] XRD refinement and quantitative analysis were performed on the powder sample after the reaction in step 5 reached the termination point to determine the mass fraction W of the amorphous phase after the precursor alkali excitation reaction. a And the mass fraction of the main crystalline phase material W i According to formula (9), the weighted average density ρ of the base-excited reaction product is determined product ; =

[0093] ρ product =W a ·ρ a +W i ·ρ i (9)

[0094] Among them, ρ a + is the density of amorphous phase, ·ρ i is the density of the main crystalline phase material, determined by experience or manual;

[0095] Step 7: Use a laser particle size analyzer to determine the particle size distribution D of the precursor powder and aggregate;

[0096] Step 8: Calculate the original density ρ of each precursor powder origin The reaction coefficient is obtained by subtracting the corresponding ratio from 1 to the weighted average density of the reaction products of the precursor powder and different types of alkali activators determined in step 6 and then multiplying the reaction degree of the corresponding alkali activator precursor powder by the molar composition coefficient of the corresponding type of alkali activator in the UHPGC formula;

[0097] Subtract the reaction coefficients corresponding to all types of alkaline activators from 1 to obtain the particle size correction coefficient of the precursor powder;

[0098] The product of the correction coefficient and D is taken as the particle size D' of the precursor powder after the reaction;

[0099] Step 9: According to the particle size D' of the precursor powder after reaction determined in step 8 and the original particle size of the aggregate, the diameter of the largest particle and the diameter of the smallest particle in the system are determined, and substituted into the MAA model to obtain the volume fraction P(D') of particles smaller than D', and then obtain the mix ratio of UHPGC;

[0100] Step 10: Based on step 9, select the steel fiber volume fraction with the best compressive strength and fluidity as the final steel fiber dosage, and calculate the steel fiber mass M 钢纤维 ;

[0101] Step 11: Carry out trial mix according to the final formula determined in step 10 and evaluate whether the compressive strength of the concrete is not less than the target compressive strength. If it is not less than, end the mix design; if it is less than, return to step 3 to adjust the mix parameters and the amount of each component.

[0102] In the present invention, the alkali excitation reaction time, reaction degree, and weighted average density can be prepared into a comparison table based on a large number of experiments and various precursor powders collected. In the later design, it can be determined by looking up the table, eliminating the previous test process, and directly obtaining the corrected particle size D' according to step seven for subsequent determination of the mix ratio, making the method more simple and practical.

[0103] Example 1

[0104] This embodiment considers the reaction of the close-packed UHPGC mix design method. Before determining the compressive strength and fluidity of the UHPGC, the UHPGC raw materials are first determined. The UHPGC raw materials are composed of steel slag powder, mineral powder, F-grade fly ash, silica fume, 40-80 mesh quartz sand, short straight steel fiber, flaky sodium hydroxide, powdered anhydrous sodium silicate and water. The specific mix design method steps are:

[0105] Step 1: Determine the target compressive strength and target fluidity of the UHPGC to be prepared, as well as the maintenance system;

[0106] Step 2: Determine the total mass M of the precursor powder 前总 And the type of precursor powder; the precursor powder is a gelling material, which refers to the material in UHPGC that can react with the alkaline activator.

[0107] Step 3: Determine the composition of the alkaline activator. In this embodiment, the alkaline activator is composed of sodium silicate and sodium hydroxide, a total of two types, the molar ratio of Na2O in sodium silicate and sodium hydroxide is n1(Na2O) / n2(Na2O), alkali-binder ratio (m(Na2O) / m(B)) and water-binder ratio (W / B), wherein n1 and n2 are the amounts of substances in moles mol; the alkali-binder ratio is the ratio of the mass of Na2O contained in the alkaline activator used in the UHPGC mix ratio to the total mass of the precursor powder, and the water-binder ratio is the ratio of water to the total mass of the precursor powder.

[0108] Step 4: Determine the alkali excitation reaction time of the precursor powder:

[0109] According to the type of alkaline activator determined in step three, sodium hydroxide activator and sodium silicate activator are prepared respectively (the mass of sodium oxide in the two is 4% of the total mass of each precursor powder, and the reaction heat test method is used to determine the reaction time when each precursor powder reacts with the sodium hydroxide activator and the sodium silicate activator to reach the exothermic steady state; the amount of each precursor powder used in the test process is the same.

[0110] Step 5: Determine the degree of alkali excitation reaction of the precursor powder:

[0111] Determine the alkali excitation reaction time of each precursor powder and each alkali exciter in step 4, and use it as the termination point of the reaction equilibrium to perform the alkali excitation reaction. After the reaction equilibrium is reached, filter, dry, and grind, and then perform a two-step selective dissolution method to determine the alkali excitation reaction degree of each precursor powder. Different solvents can be selected for each precursor powder.

[0112] Specifically, according to the configuration quality of step 4, sodium hydroxide activator and sodium silicate activator were prepared respectively, and the mass fractions C of NASH gel and CASH gel generated when each precursor powder reacted with sodium hydroxide activator and sodium silicate activator to reach the exothermic steady state were determined by two-step selective dissolution method. nash , C cash and reaction degree γ, the operation steps are as follows:

[0113] ① Sample preparation: Mix the precursor powder with the alkaline activator and use a magnetic stirrer to continuously stir until the reaction time is over. After the reaction is completed, filter it immediately using a vacuum filtration device (with a pore size of at least 0.45 μm). Dry the filter residue in a vacuum drying oven at 105°C to constant weight. Then grind the dried filter residue into powder as the first selective dissolution sample and store it in a sealed manner for use in the selective dissolution test.

[0114] ② The first step of selective dissolution: take the sample prepared in ①, and for the first selective dissolution sample of each precursor powder, take 4 portions, each of 1 g, and mix each portion with 1 portion of a selective dissolving agent (depending on the type of precursor powder, this embodiment uses salicylic acid-methanol solution) and continue stirring for 60 minutes. After the reaction is completed, filter it immediately with a vacuum filtration device (pore size of 0.45 μm), and place the filter residue in a vacuum drying oven and dry it at 105°C to constant weight to obtain the second selective dissolution sample, and record the final mass as M1.

[0115] ③ The second step of selective dissolution: take the filter residue obtained from the first step of selective dissolution as a sample. Take 3 portions of the second selective dissolution sample of each precursor powder, each portion is 1 g, and each sample is mixed with a selective dissolving agent (depending on the type of precursor powder, this embodiment uses dilute hydrochloric acid or EDTA solution as the second selective dissolving agent) and stirred continuously for 60 minutes. After the reaction is completed, filter it immediately with a vacuum filtration device (pore size of 0.45 μm), and place the filter residue in a vacuum drying oven and dry it at 105°C to constant weight. The final mass is recorded as M2.

[0116] After the test, the mass fractions of NASH and CASH gels generated when the alkaline activators are NaOH and Na2SiO3 respectively, as well as the reaction degrees γ1 and γ2, were calculated according to formulas (3) to (5).

[0117] C nash =(M0-M1) / M0×100% (3)

[0118] C cash =(100%-C nash )×(M2-M3) / M2 (4)

[0119] γ=C nash +C cash (5)

[0120] Among them, C nash is the mass fraction of the sample dissolved in the selective dissolution solution in the first step of selective dissolution, that is, the mass fraction of NASH gel in the sample; M0 is the mass of the sample used in the first step of selective dissolution (g), taking 1g; M1 is the remaining mass of the sample after the first step of selective dissolution (g). cash is the mass fraction of the sample dissolved in the selective dissolution solution in the second step of selective dissolution, that is, the mass fraction of CASH gel in the sample; M2 is the mass of the sample used in the second step of selective dissolution (g), taking 1g; M3 is the remaining mass of the sample after the second step of selective dissolution (g).

[0121] Step 6: Determine the weighted average density of the precursor powder alkali excitation reaction product:

[0122] Perform XRD refinement and quantitative analysis on the powder sample after the reaction in step 5 reaches the termination point, and determine the product density based on the phase composition and corresponding mass fraction of the main reaction product after the precursor alkali excitation reaction;

[0123] This application adopts the internal standard method, using α-Al2O3 as the internal standard. The operation steps are as follows:

[0124] ① Sample preparation: Mix the precursor powder with the alkaline activator and use a magnetic stirrer to stir continuously until the reaction time is over. After the reaction is completed, filter it immediately using a vacuum filtration device (pore size of 0.45 μm), place the filter residue in a vacuum drying oven and dry it to constant weight at 105°C, then grind the dried filter residue into powder (the same as in step 5), then weigh the ground powder, add 10% mass fraction of α-Al2O3 and continue grinding for 5 minutes to fully mix the internal standard and the sample, and finally seal the mixed sample for storage for XRD refinement analysis.

[0125] ②XRD scanning and phase analysis: Perform XRD scanning on the sample obtained in ①, and use Jade6.5 software to perform phase analysis on the obtained XRD spectrum to find out the main crystalline phase contained in the sample (the main crystalline phase refers to the crystalline phase with a mass proportion of not less than 5% in the XRD refinement analysis sample).

[0126] ③XRD refinement: The XRD pattern obtained by scanning was subjected to Rietveld refinement analysis, and the amorphous phase content W of the sample doped with internal standard was A Calculated by formula (6):

[0127]

[0128] Where W S is the mass fraction of the internal standard added to the sample, W R is the mass fraction of the internal standard calculated by refinement.

[0129] After removing the internal standard in the sample, the mass fraction W of the amorphous phase in the precursor powder after the reaction can be calculated according to equations (7) and (8): a And the mass fraction of the main crystalline phase material W i , combined with the mass fraction C of the amorphous gel phase obtained in the selective dissolution test nash and C cash , the crystalline phase and amorphous phase composition in the precursor powder after the reaction can be fully determined. According to the corresponding density, the weighted average density of the precursor powder after the reaction can be calculated according to formula (9).

[0130]

[0131] Where W i,R is the mass fraction of the crystalline phase obtained by refinement calculation.

[0132] ρ product =W a ·ρ a +W i ·ρ i (9)

[0133] Among them, ρ a + is the density of amorphous phase, ·ρ i is the density of the main crystalline phase material, determined by experience or manual;

[0134] Step 7: Use a laser particle size analyzer to determine the particle size distribution D of the precursor powder and aggregate;

[0135] Step 8: Calculate the particle size D' of the precursor powder after reaction according to formula (10), and correct the particle size of each precursor powder.

[0136]

[0137] in α1 and α2 are the molar composition coefficients of sodium oxide in sodium hydroxide and sodium silicate, respectively; n1(Na2O) and n2(Na2O) are the amounts of Na2O contained in sodium hydroxide and sodium silicate in the actual mix ratio; γ1 and γ2 represent the degree of reaction of the precursor powder when sodium hydroxide and sodium silicate are used as alkaline activators, respectively; ρ origin is the original density of the precursor powder, ρ product1 , ρ product2 are the weighted average densities of the precursor powder reaction products when sodium hydroxide and sodium silicate are used as alkaline activators, respectively.

[0138] Step 9: According to the particle size D' of the precursor powder after reaction determined in step 8 and the original particle size of the aggregate, the diameter of the largest particle and the diameter of the smallest particle in the system are determined, and substituted into the MAA model to obtain the volume fraction P(D') of particles smaller than D', and then obtain the mix ratio of UHPGC; the specific formula is formula (11)

[0139]

[0140] Where P(D') is the volume fraction of particles with a diameter smaller than D';

[0141] D' is the particle size after the reaction;

[0142] D' min is the diameter of the smallest particle in the system;

[0143] D' max is the diameter of the largest particle in the system;

[0144] q is the distribution modulus (0.2-0.5);

[0145] In order to maximize the packing density of the system, it is necessary to minimize the error between the target value and the fitted value, that is, to satisfy formula (12):

[0146]

[0147] in and Respectively represent the percentage of the particle size between the i-th particle size and the i+1-th particle size in the actual stacking curve and the ideal stacking curve from small to large, RSS is the residual sum of squares, and TSS is the total sum of squares. 2 The value range is 0.95-1.

[0148] Step 10: Based on step 9, determine the amount of steel fiber added to achieve the best compressive strength and fluidity. According to the test, determine the change rules of compressive strength and fluidity of UHPGC with steel fiber volume fractions of 1%, 2%, and 3%, select the optimal steel fiber volume fraction and calculate the steel fiber mass M.钢纤维 ;

[0149] Step 11: Carry out trial mix according to the final formula determined in step 10 and evaluate whether the compressive strength of the concrete is not less than the target compressive strength. If it is not less than, end the mix design; if it is less than, return to step 3 to adjust the mix parameters and the amount of each component.

[0150] Example 2

[0151] In this embodiment, the precursor powders are fly ash, mineral powder and steel slag powder, and the process of the two-step selective dissolution method is:

[0152] ① Sample preparation: Mix the precursor powder with the alkaline activator and use a magnetic stirrer to continuously stir until the reaction time is over. After the reaction is completed, filter it immediately using a vacuum filtration device (pore size of 0.45 μm), place the filter residue in a vacuum drying oven at 105°C and dry it to constant weight, then grind the dried filter residue into powder and store it in a sealed container for use in selective dissolution tests.

[0153] ② The first step of selective dissolution: Take the prepared samples after the alkali excitation reaction. For each sample of the precursor powder, take 4 portions, each weighing 1 g. Mix each portion with 1 portion of salicylic acid-methanol solution (prepared by dissolving 3 g of salicylic acid solid in 50 mL of methanol) and continue stirring for 60 minutes. After the reaction is completed, filter it immediately with a vacuum filtration device (pore size of 0.45 μm), and dry the filter residue in a vacuum drying oven at 105°C to constant weight. Record the final mass as M1.

[0154] ③ The second step of selective dissolution: take the filter residue obtained by the selective dissolution in the first step as the sample. For each sample of the precursor powder, take 3 portions, each weighing 1 g. For the fly ash sample, each portion is mixed with 250 mL of dilute hydrochloric acid (0.5 mol / L) and stirred continuously for 60 minutes. For the slag and steel slag samples, each portion is mixed with 1 portion of standard EDTA solution (4.6 g of EDTA-2Na solid is fully dissolved in 75 mL of water and the volume is adjusted to 100 mL), 3 g of triethanolamine, and 120 mL of water and stirred continuously for 60 minutes. After the reaction is completed, filter it immediately with a vacuum filtration device (pore size of 0.45 μm), and dry the filter residue in a vacuum drying oven at 105°C to constant weight. The final mass is recorded as M3.

[0155] After the test, the mass fractions of NASH and CASH gels generated when the alkaline activators are NaOH and Na2SiO3 respectively, as well as the reaction degrees γ1 and γ2, were calculated according to formulas (3) to (5).

[0156] Among them, C nashis the mass fraction of the sample dissolved in the SAM solution, that is, the mass fraction of NASH gel in the sample; M0 is the original mass of the sample (g), taking 1g; M1 is the remaining mass of the sample after the first step of selective dissolution (g). cash It is the mass fraction of the sample dissolved in dilute hydrochloric acid or EDTA solvent, that is, the mass fraction of CASH gel in the sample; M2 is the mass of the sample used in the second step of selective dissolution (g), taking 1g; M3 is the remaining mass of the sample after the second step of selective dissolution (g).

[0157] Step 6: Determine the density of the precursor powder alkali excitation reaction product, using α-Al2O3 as the internal standard. The operation steps are as follows:

[0158] ① Sample preparation: Prepare the precursor powder sample after the alkali excitation reaction, mix the precursor powder with the alkali activator and use a magnetic stirrer to continuously stir until the reaction time is over. After the reaction is completed, immediately filter it using a vacuum filtration device (pore size of 0.45 μm), place the filter residue in a vacuum drying oven and dry it to constant weight at 105°C, then grind the dried filter residue into powder, then weigh the ground powder, add 10% mass fraction of α-Al2O3 and continue grinding for 5 minutes to fully mix the internal standard and the sample, and finally seal the mixed sample for storage for XRD refinement analysis.

[0159] ②XRD scanning and phase analysis: XRD scanning was performed on the sample, and the obtained XRD spectrum was used for phase analysis using Jade 6.5 software to find out the main crystalline phase contained in the sample.

[0160] ③XRD refinement: The XRD pattern obtained by scanning was subjected to Rietveld refinement analysis, and the amorphous phase content W of the sample doped with internal standard was A Calculated by formula (6).

[0161] After removing the internal standard in the sample, the mass fraction W of the amorphous phase in the precursor powder after the reaction can be calculated according to equations (7) and (8): a And the mass fraction of the main crystalline phase material W i ...combined with the mass fraction of the amorphous gel phase C obtained from the selective dissolution test nash and C cash , the crystalline phase and amorphous phase composition in the precursor powder after the reaction can be fully determined. According to the corresponding density, the weighted average density of the precursor powder after the reaction can be calculated according to formula (9).

[0162] Step 7: Use a laser particle size analyzer to determine the particle size distribution D of the precursor powder and aggregate;

[0163] Step 8: Calculate the particle size D' of the precursor powder after the reaction according to formula (10)

[0164] Step 9: According to the particle size D' of the precursor powder after reaction determined in step 8 and the original particle size of the aggregate, the diameter of the largest particle and the diameter of the smallest particle in the system are determined, and substituted into the MAA model to obtain the volume fraction P(D') of particles smaller than D', and then obtain the mix ratio of UHPGC;

[0165] In order to maximize the packing density of the system, it is necessary to minimize the error between the target value and the fitted value, that is, to satisfy equation (12).

[0166] Step 10: According to the test, the compressive strength and fluidity change rules of UHPGC with steel fiber volume fractions of 1%, 2%, and 3% are determined, and the optimal steel fiber volume fraction is selected and the steel fiber mass M is calculated. 钢纤维 ;

[0167] Step 11: Conduct trial mix and evaluate whether the material properties of concrete meet the requirements. If so, end the mix design; if not, return to step 3 to adjust the mix parameters and the amount of each component.

[0168] Example 3: In this example, before determining the compressive strength of UHPGC, the raw materials of UHPGC are first determined. The raw materials of UHPGC are composed of steel slag powder, mineral powder, F-grade fly ash, silica fume, 40-80 mesh quartz sand, short straight steel fiber, flaky sodium hydroxide, powdered anhydrous sodium silicate and water. The other steps are the same as those in specific example 2.

[0169] Example 4: The curing system in step 1 of this example is 80°C oven curing for 48 hours, which can ensure that the UHPGC quickly reaches the target strength and shortens the curing period; and 80°C oven curing is also beneficial to reduce the cracking risk of UHPGC, compact the microstructure, and improve the durability of concrete. The other steps are the same as in Example 1 or 2.

[0170] Embodiment 5: The curing system of step 1 of this embodiment also includes a stirring system, including the following steps:

[0171] Step 1: Mix the precursor powder and aggregate and stir for 2 minutes;

[0172] Step 2: Add the activator determined in step 3 and stir at low speed (140r / min) for 2 minutes;

[0173] Step 3: Add the steel fiber determined in step 10 and stir at high speed (280r / min) for 1 minute. The test method is: the compressive strength test is carried out using a 50×50×50mm 3 Cube test block, the test block loading system is 0.6MPa / s.

[0174] It ensures that there is no risk of fiber agglomeration during the concrete mixing process, and ensures that the concrete components are fully mixed to obtain a more uniform UHPGC.

[0175] Example 6: The short straight steel fiber of this example has a diameter of 0.2 mm and a length of 13 mm, which can ensure the basic static mechanical properties of UHPGC and improve its impact resistance under dynamic loads.

[0176] Example 7: The total amount of precursor powder in step 2 of this example M 前总 =800-1100kg / m 3 . Suitable for most ultra-high performance concrete.

[0177] Example 8: The compressive strength of the UHPGC to be prepared in step 1 of this example is 100 MPa-150 MPa. The range of concrete suitable for preparation is relatively wide.

[0178] Example 9: Before using the MAA close packing model formula to calculate the mass fraction of each component of the UHPGC raw material, the particle size after the alkali excitation reaction is determined according to the alkali excitation reaction degree of the precursor powder and the composition of the reaction product.

[0179] Embodiment 10:

[0180] Step 1: Prepare UHPGC with a compressive strength of 120 MPa and a fluidity of 260 mm;

[0181] Step 2: Define the powder that can react with the alkaline activator as the precursor powder, determine the type of UHPGC precursor powder, and set the total mass of the precursor powder;

[0182] Step 3: Select the molar ratio of Na2O in sodium silicate and sodium hydroxide n1(Na2O) / n2(Na2O)=2.5, the alkali-binder ratio N / B=4%, and the water-binder ratio W / B=0.26;

[0183] Step 4: Determine the reaction time of steel slag powder, fly ash and mineral powder to be 30 minutes by reaction heat test with the proportion shown in the following table;

[0184] Unit: g

[0185]

[0186] The reaction time is determined according to the reaction heat curve. In the embodiment, the reaction heat curves of the three precursor powders can all reach stability at 30 minutes and the difference is not large. For the sake of simplicity, 30 minutes is uniformly selected as the reaction time.

[0187] Step 5: The samples for the two-step selective dissolution test were prepared in the ratios shown in the following table. For the first step of the selective dissolution test, 1 g of each sample was taken, 4 portions were mixed with 1 portion of salicylic acid-methanol solution and stirred for 1 hour, and the mixture was vacuum filtered (0.45 μm pore size) and dried in a vacuum drying oven at 105°C to constant weight. For the second step of the selective dissolution test, 1 g of the filter residue from the first step was taken. For the mineral powder and steel slag powder samples, it was mixed with 1 portion of EDTA solution and stirred for 1 hour. For the fly ash samples, it was mixed with 1 portion of dilute hydrochloric acid and stirred for 1 hour. The mixture was vacuum filtered (0.45 μm pore size) and dried in a vacuum drying oven at 105°C to constant weight. The test results are calculated according to formulas (3), (4), and (5) to obtain the mass fractions C of the generated NASH gel and CASH gel. nash , C cash And the reaction degree γ:

[0188] Unit: g

[0189]

[0190]

[0191] The results are as follows:

[0192]

[0193] Step 6: Prepare the sample for XRD quantitative analysis test. The sample is the same as the sample for selective dissolution test, and 10% mass fraction of α-alumina is added. The composition and corresponding density of the obtained reaction product are shown in the following table

[0194]

[0195] Step 7: Use a laser particle size analyzer to determine the particle size distribution of steel slag powder, fly ash, mineral powder, silica ash, and quartz sand. Figure 3 As shown;

[0196] Step 8: According to formula (10), the particle size of the steel slag powder after the reaction is 1.1 times the original particle size, the particle size of the fly ash is 1.01 times the original particle size, and the particle size of the mineral powder is 1.09 times the original particle size.

[0197] The above are general steps. Step 9 is explained according to different control examples and examples.

[0198] Step 9: Control example: without any restrictions, the dosage ratio of each component of UHPGC is calculated according to the original particle size of the precursor powder and aggregate and the MAA model formula (1) and the least square method (2);

[0199] Example 1: The mass fraction of silica fume is fixed at 10% of the total mass of the precursor powder, and the dosage ratio of each component of UHPGC is calculated according to the particle size of the precursor powder and aggregate after the reaction and the modified MAA model formula (11) and the least square method (12);

[0200] Example 2: The mass fraction of silica fume is fixed at 12% of the total mass of the precursor powder, and the dosage ratio of each component of UHPGC is calculated according to the particle size of the precursor powder and aggregate after the reaction and the modified MAA model formula (11) and the least square method (12);

[0201] Example 3: The mass fraction of silica fume is fixed at 14% of the total mass of the precursor powder, and the dosage ratio of each component of UHPGC is calculated according to the particle size of the precursor powder and aggregate after the reaction and the modified MAA model formula (11) and the least square method (12);

[0202] Step 10: According to the test, the compressive strength and fluidity change rules of UHPGC with steel fiber volume fractions of 1%, 2%, and 3% are as shown in the following table, and steel fiber with a volume fraction of 2% is selected;

[0203] Steel fiber content Compressive strength(MPa) Fluidity(mm) 1% 104.2 282 2% 137.2 261 3% 141.2 205

[0204] Step 11: Conduct trial mix and evaluate whether the performance of concrete meets the requirements. If so, end the mix design; if not, return to step 2 to adjust the mix parameters and the amount of each component;

[0205] The complete configuration in this embodiment is shown in the following table:

[0206]

[0207] Test results:

[0208] Compressive strength(MPa) Fluidity(mm) Comparison Example 102.9 221 Example 1 120.8 284 Example 2 111.5 242 Example 3 137.6 261

[0209] In the above table, both Example 1 and Example 3 meet the set requirements, and the method ends when a mix ratio that meets the requirements is found.

[0210] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above examples, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

[0211] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A method for designing a close-packed UHPGC mix ratio considering reactions, characterized in that: The steps of the design method are: Step 1: Determine the target compressive strength and target fluidity of the UHPGC to be prepared, as well as the maintenance system; Step 2: Define the powder that can react with the alkaline activator as the precursor powder, and determine the type of UHPGC precursor powder; Step 3: Determine the type of alkali activator and the molar number of Na2O in different types of alkali activators, and simultaneously determine the alkali-binder ratio (N / B) and the water-binder ratio (W / B); wherein the alkali-binder ratio is the ratio of the mass of Na2O contained in the alkali activator used in the UHPGC mix ratio to the total mass of the precursor powder, and the water-binder ratio is the ratio of water to the total mass of the precursor powder; Step 4: Determine the alkali excitation reaction time of each precursor powder: The reaction heat test method is used to determine the reaction time when each precursor powder reacts with each alkaline activator to reach the exothermic steady state; The precursor powders of different types are set to have the same mass, denoted as A0, and the mass of sodium oxide in each alkaline activator is set to 4% A0; Step 5: Determine the degree of alkali excitation reaction of the precursor powder: Determine the alkali excitation reaction time of each precursor powder and each alkali exciter in step 4, and use it as the termination point of the reaction equilibrium to perform the alkali excitation reaction. After the reaction equilibrium is reached, filter, dry, and grind, and then perform a two-step selective dissolution method to determine the alkali excitation reaction degree of each precursor powder. Different solvents can be selected for each precursor powder. The process of the two-step selective dissolution method is: The first step is to select a first selective solvent that cannot dissolve the precursor powder and the alkali-activated product CASH gel, but can dissolve the alkali-activated product NASH gel, and dissolve the sample that has reached the reaction equilibrium termination point in the first selective solvent for 1 hour; after the dissolution is completed, filter and dry, and record the mass as M1; Step 2: Select a second selective solvent that cannot dissolve the precursor powder but can dissolve the alkali-activated product CASH gel, and dissolve the material filtered and dried in the first step in the second selective solvent for 1 hour. After dissolution, filter and dry to constant weight, and record the mass as M3; Then, according to formulas (3)-(5), the mass fraction C of NASH gel generated at reaction equilibrium is obtained: nash and CASH gel mass fraction C cash and the degree of reaction γ; C nash =(M0-M1) / M0×100% (3) <h2 style=";text-align:left;direction:ltr">C<h2 style=";text-align:left;direction:ltr"> cash <h2 style=";text-align:left;direction:ltr"> (100%)<h2 style=";text-align:left;direction:ltr"> nash <h2 style=";text-align:left;direction:ltr"> )×(M2-M3) / M2 (4) γ=C nash +C cash (5) Wherein, M2 is the mass of material used in the second step of selective dissolution; M0 is the mass of sample used in the first step of selective dissolution; Step 6: Determine the weighted average density of the precursor powder alkali excitation reaction product: XRD refinement and quantitative analysis were performed on the powder sample after the reaction in step 5 reached the termination point to determine the mass fraction W of the amorphous phase after the precursor alkali excitation reaction. a And the mass fraction of the main crystalline phase material W i According to formula (9), the weighted average density ρ of the base-excited reaction product is determined product ; r product =W a ·r a +W i ·r i (9) Among them, ρ a + is the density of amorphous phase, ρ i is the density of the main crystalline phase material; Step 7: Use a laser particle size analyzer to determine the particle size distribution D of the precursor powder and aggregate; Step 8: Calculate the original density ρ of each precursor powder origin The reaction coefficient is obtained by subtracting the corresponding ratio from 1 to the weighted average density of the reaction products of the precursor powder and different types of alkali activators determined in step 6 and then multiplying the reaction degree of the corresponding alkali activator precursor powder by the molar composition coefficient of the corresponding type of alkali activator in the UHPGC formula; Subtract the reaction coefficients corresponding to all types of alkaline activators from 1 to obtain the particle size correction coefficient of the precursor powder; The product of the correction coefficient and D is taken as the particle size D' of the precursor powder after the reaction; Step 9: According to the particle size D' of the precursor powder after reaction determined in step 8 and the original particle size of the aggregate, the diameter of the largest particle and the diameter of the smallest particle in the system are determined, and substituted into the MAA model to obtain the volume fraction P(D') of particles smaller than D', and then obtain the mix ratio of UHPGC; Step 10: Based on step 9, select the steel fiber volume fraction with the best compressive strength and fluidity as the final steel fiber dosage, and calculate the steel fiber mass M 钢纤维 ; Step 11: Carry out trial mix according to the final formula determined in step 10 and evaluate whether the compressive strength of the concrete is not less than the target compressive strength. If it is not less than, end the mix design; if it is less than, return to step 3 to adjust the mix parameters and the amount of each component.

2. The design method according to claim 1, characterized in that: The number of types of the base activators is not less than 1.

3. The design method according to claim 1, characterized in that: The alkaline activators are sodium silicate and sodium hydroxide. The particle size D' of each precursor powder after reaction is expressed by formula (10): in, α1 and α2 are the molar composition coefficients of sodium oxide in sodium hydroxide and sodium silicate, respectively; n1(Na2O) and n2(Na2O) are the amounts of Na2O contained in sodium hydroxide and sodium silicate in the actual mix ratio; γ1 and γ2 represent the degree of reaction of the precursor powder when sodium hydroxide and sodium silicate are used as alkaline activators, respectively; ρ origin is the original density of the precursor powder, ρ product1 , ρ product2 are the weighted average densities of the precursor powder reaction products when sodium hydroxide and sodium silicate are used as alkaline activators, respectively.

4. The design method according to claim 1, characterized in that: The XRD refinement quantitative analysis uses α-Al2O3 as an internal standard. After the precursor powder and the alkaline activator react to the termination point, they are filtered, dried to constant weight and ground. The ground powder is weighed and 10% of the powder mass of α-Al2O3 is added and continued to grind so that the internal standard and the powder are fully mixed, and then XRD refinement analysis is performed; the main crystal phase refers to the crystal phase whose mass accounts for not less than 5% in the XRD refinement analysis sample.

5. The design method according to claim 1, characterized in that: In the two-step selective dissolution method, each precursor powder can select a different solvent, and the order of the first and second steps of selective dissolution can be swapped. The first selective dissolution agent after the swap is a solvent that cannot dissolve the precursor powder and NASH gel, but can dissolve the alkali-excited product CASH gel. The sample that reaches the reaction equilibrium termination point is dissolved in the first selective dissolution agent for 1 hour; after the dissolution is completed, the mass is filtered and dried and recorded as M1, which is used to calculate the mass fraction C of CASH gel cash ; At this time, the second selective dissolving agent cannot dissolve the precursor powder, but can dissolve the alkali-activated product NASH gel. The material filtered and dried in the first step is dissolved in the second selective dissolving agent for 1 hour. After the dissolution is completed, it is filtered and dried to a constant weight. The mass is recorded as M3, which is used to calculate the mass fraction C of NASH gel. nash .

6. The design method according to claim 1, characterized in that: The first selective dissolving agent is at least one of salicylic acid-methanol solution and picric acid-methanol-water solution; the second selective dissolving agent is at least one of dilute hydrochloric acid, EDTA solution and EDTA / DEA solution.

7. The design method according to claim 1, characterized in that: In the step nine, when determining the mix ratio of UHPGC, the mass percentage range of silica fume is set, and the mix ratio of UHPGC is determined under this premise.

8. The design method according to claim 1, characterized in that: The curing system is high temperature curing or steam curing, and the curing temperature is any temperature between 50°C and 90°C; preferably, the curing system also includes a stirring system; The pore size of the filter assembly used in the filtration is not less than 0.45 μm; The target compressive strength is 100MPa-150MPa.